Meta-Analysis of the Efficacy and Safety Evaluation of Vandetanib in the Treatment of Medullary Thyroid Cancer - Xian, Tong-cheng; Yang, Min-ye; Zhang, Xue-lin; Wang, Jie; Luo, Yi (Hormone and Metabolic Research, 2024)
The aim of the work was to systematically evaluate the efficacy and safety of Vandetanib in the treatment of advanced medullary thyroid carcinoma (MTC). MeSH entries to search for randomized controlled trials and clinical research literature on the application of Vandetanib in the treatment of medullary thyroid cancer from PubMed, Chinese national knowledge infrastructure (CNKI), and Web of Science databases since their establishment until March 2023 were used. In terms of efficacy, the analysis results showed that Vandetanib had a significantly higher objective response rate compared to the control group using placebo (OR=2.13, 95% CI: 1.38, 3.29). In terms of side effects, Vandetanib significantly increases the incidence of hypertension, rash, and diarrhea, and has statistical significance (p+<+0.05). Vandetanib has a better therapeutic effect on MTC, but it also increases the incidence of hypertension, rash, and diarrhea. Attention should be paid to the relief of side effects when using it.
Keywords: medullary thyroid carcinoma; Vandetanib; objective response rate; side effects; meta-analysis